Constructing Social Critique as Ethical Discourse in Indonesian Popular Religious Literature: A Content Analysis of Husein Ja‘far Al-Hadar’s Tuhan Ada di Hatimu - Ahmad Farid Fanani; Muhammad Taufik; Aisah Bella-Salsa; Muhammad Zainal Abidin; Muhammad Yusuf Pratama (Jurnal Lektur Keagamaan, 2026)
Religious intolerance and exclusivism remain challenges in Indonesia’s plural society, particularly when religious practices tend to be confined to symbolism and formalism that do not adequately reflect ethical values. Previous studies have positioned religious literature as a medium for transmitting moral and inclusive values; however, most of them focus on normative and philosophical aspects and provide limited empirical explanation of how social critique is constructed and articulated within popular religious works. This gap is significant given the broad reach of popular literature in shaping public perceptions of religious practice. Addressing this gap, this study aims to analyze the forms of social critique in Tuhan Ada di Hatimu (God Resides in Your Heart) by Husein Ja‘far Al-Hadar and examine their relevance to contemporary Indonesian religiosity. The study employs a qualitative library-based approach using content analysis to identify key themes of critique, including excessive conservatism, judgmental culture, and the politicization of religious symbols. The findings show that the work not only reflects socio-religious conditions but also constructs critique through a narrative that emphasizes self-reflection, empathy, and contextual understanding of religious teachings. These results indicate that popular religious literature can function as a medium for articulating social critique that bridges religious texts and social realities. Theoretically, this study contributes by demonstrating how content analysis can be used to uncover the construction of social critique in popular religious narratives, while also expanding discussions on religious literature as a site for articulating social critique within contemporary religiosity.